The perceptions of self-assessment in basic education in craft, design and technology - Sari Saarnilahti; Eila Lindfors (Malta, 2022)
This article examines the perceptions and occurrence of self-assessment of sixth and ninth grade, 12 and 16 years old students (N = 508) and the different ways that self-assessment was carried out during a holistic craft process. The study was conducted in the context of the Finnish comprehensive education Basic Education curricula of 2004 and 2014.
The goal of self-assessment is to develop students’ learning process. Self-assessment is an integral part of a holistic design and making process in craft, design and technology (CDT) education. Self-assessment can be implemented through evidence based, reinforcing, reflective and pragmatic self-assessment. Self-assessment is a part of design, planning and manufacturing a product. It can occur in every step of the process, also as the final assessment of the work.
The data was collected in town schools in comprehensive primary and secondary education in Finland in 2017. The summation-based analysis showed that there were statistically significant differences between student groups. The ninth grade students who did not study
CDT as an optional subject expressed the most negative perceptions in all areas of self-assessment. Getting used to self-assessment was clearly associated with the students' positive perceptions towards self-assessment as a part of a learning process. The data from open-ended questions were in line with the result of the analysis.
Although the data of the study was collected in a geographically limited area, it gives an idea how students see self-assessment as a part of their learning. The results suggest the importance for students to acquire self-assessment skills not only as an important stage of their learning process but also from the positive learning experience point of view.
Proceedings PATT 37 : Developing a knowledge economy through technology and engineering education, 3-6 June 2019, University of Malta, Msida Campus